Mediating effect of network competence on relationship between technology usage, human capital and organizational performance of medium-sized enterprises in Lagos State, Nigeria - Eze, Ezuma Kingsley (2019)
The review of past literature has shown that considerable attention has been given to organizational performance and its potential factors in various sectors. However, not much emphasis has been laid on the issue of human capital predictors such as management skill, leadership skill, knowledge creation, ICT usage and the mediating effect of network competence particularly in the medium-sized manufacturing enterprises in the Lagos state, Nigeria. Therefore, this study examines the mediating effect of network competence on the relationship between human capital practices and v Organizational Performance of Manufacturing Medium Sized enterprises. Theories of human capital and resource based, were used to explain the variables in the study. This study was conducted based on 245 samples involving owners of manufacturing medium sized enterprises who were administered with structured questionnaire. Statistical Package for Social Sciences (SPSS) was used for descriptive analysis (mean values, frequencies and percentages) and Structural Equation Modelling (SEM) using AMOS was employed for inferential statistics. Additionally, SEM was applied to test and establish the existence of convergent validity and discriminant validity of the measured constructs. Prior to the utilization of the model, the measurement model confirmed the appropriateness of the data with x2(959) =1434.521; P=0.000; x2/DF=1.496; GFI=0. 801; CFI=0.938; IFI=0.939; TLI=0.933; RMSEA =.045. The descriptive analysis showed that organizational performance were practiced at high level while the other variables tested in this study were at moderate. Based on results from the structural model, it can be deduced that network competence partially and fully mediates the relationship between human capital predictors and Organizational Performance, which could mean that improved network competency will positively impact on human capital predictors leading to an improved organizational performance in medium-sized manufacturing SMEs. This could also serve as a guiding principle for organizations to adopt human capital related to skills development of individuals and network competencies. The implications for practice is that the study will enable the adoption of an vi appropriate HRD approach that would involve development of skills for management and leadership concerns of enterprises through training, organizational development and career development. This study has shown that network competence is the mechanism through which human capital predictors influence the organizational performance of medium sized enterprises in Nigeria. However, there is no significant relationship between ICT usage, network competence and organizational performance of medium sized manufacturing enterprises in the context of Lagos state Nigeria. Therefore, more research is needed in the area of ICT adaptation and usage because advanced technology application is of great significance in most developed countries.